HDQ-based solution strategy for in-plane nonlinear buckling of shallow steel arches with linear elastic supports - Zhang, Zixiang; Wang, Weile; Liu, Yuanyuan; Pan, Junjie; Xin, Weijin (Frontiers in Physics, 2025)
This paper investigates the in-plane nonlinear buckling of shallow steel arches with linear elastic supports. Differential equations of equilibrium are built considering a virtual work principle. To balance computational accuracy, efficiency, and cost, a harmonic differential quadrature method (HDQ)-based solution strategy combined with an iterative process is utilized to follow the complete buckling path. The corresponding critical buckling load is obtained. The convergence of HDQ algorithm is then examined, and the accuracy of presented solutions is validated by comparing the FE predictions. It was found that the nonlinear behavior of circular arches with linear elastic supports can be precisely predicted by the presented HDQ-based solution strategy. The arch could buckle either in a limit point mode or a bifurcation mode, depending on the modified slenderness ratio.